Sistem pakar Diagnosa Penyakit Campak Pada Anak Dengan Menerapkan Metode Fuzzy Mamdani - Ramadhani, Nurlela (Jurnal Sains dan Teknologi Informasi, 2023)
Measles, also known as morbili in Latin and measles in English, or known as gabagen (in Banjarese) or rubeola (German measles) is a viral infection that causes chronic intrauterine infection, disrupting fetal growth and development, an infection highly contagious virus, which is characterized by fever, weakness, cough (inflammation of the connective membrane of the eye) and red spots on the skin. The group most vulnerable to contracting this disease are infants and children who have never received measles immunization. This disease is also one of the causes of high morbidity and mortality rates in infants and children. The problem of measles is that it is often difficult to detect symptoms and needs further medical treatment to find out the symptoms of measles. Ignorance of the community about traces of measles can be fatal and can even cause death. Measles is an endemic disease in developing countries, including Indonesia. Based on the results of the final calculation test at the defuzzification stage, the severity of the diagnosis of measles in children is in the definite category